Efektivitas Pelaksanaan P5 Pada Pertengahan Semester Ganjil di SMAN 1 Kota Serang - Wardani, Arum Pramudya; Pasaribu, Lidya Anastasya; Susmitasari, Puja; Irawan, Nabila Agustin; Arifin, Tubagus Rafli Zainul (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This article aims to examine and eval___uate the effectiveness of the implementation of the Strengthening Pancasila Student Profile (P5) Project in the middle of the odd semester at SMAN 1 Kota Serang. The research objective is to analyze and assess the effectiveness of the P5 implementation in the middle of the odd semester for grade X students at SMAN 1 Kota Serang. This research can be used as eval___uation material or projections by teachers, students, or relevant parties in the implementation of P5. This study uses a qualitative descriptive method. Data collection techniques include interviews conducted with 2 representatives from each class X, and observations made by the researcher by observing P5 activities, supported by various sources such as journals and academic literature. The results of the study show that the implementation of P5 at SMAN 1 Kota Serang in grade X has had a positive outcome, with students feeling more confident, creative, and able to think critically. They learned about democracy, mutual cooperation, and freedom of expression.